Synthesis, Spectral and Antibacterial Studies of Dioxotungsten(VI) Complexes of 2,3-Dimethyl-1-phenyl-4- (2-hydroxy-4-methoxyphenylazo)pyrazol-5-one - SHEELA, A.; HARI KUMARAN NAIR, M.L. (Asian Journal of Chemistry, 2010)
Some novel dioxotungsten(VI) complexes of the ligand 2,3-dimethyl-1-phenyl-4-(2-hydroxy-4-methoxyphenylazo) pyrazol-5-one (methoxyphenolazoanti-pyrine, MOPAAP) having the compositions [WO2LXCl] (X = Cl, NO3, NCS or ClO4 and L = MOPAAP) have been synthesized and characterized by elemental analysis, molar conductance, IR and 1H NMR spectral studies. The thermal behaviour of one of the complexes has also been examined. The ligand and one of its complexes were screened for their possible antibacterial activity against gram positive and gram negative bacteria. The X-ray powder diffraction patterns of one of the complexes has also been examined. The complex was found to be orthorhombic with the unit cell dimensions such as a = 5.4467 Å, b = 12.1792 Å and c = 17.2240 Å and the lattice constants A = 0.02195, B = 0.004 and C = 0.00204. The ligand behaves as neutral bidentate. The complexes are found to be non-electrolytes with octahedral geometry.